Cattleya attenboroughiana (Orchidaceae: Laeliinae): a new species from the Diamantina Plateau, Minas Gerais, Brazil - Menezes, Euler L. F.; Giordani, Samuel C. O.; Pinheiro, Rodrigo A.; Gonella, Paulo M. [UNESP] (Springer Nature, 2024)
A new species of Cattleya ser. Parviflorae (Orchidaceae) is here described from the campos rupestres of the Diamantina Plateau, part of the Espinhaço Range, Minas Gerais, SE Brazil. The new species is named Cattleya attenboroughiana and it is here compared to the most similar taxa and illustrated with photographs. The new species is likely a microendemic but the available data is insufficient for a precise conservation status assessment, so we consider it Data Deficient (DD), reinforcing the need for further exploration in the Diamantina Plateau.
Keywords: Campos rupestres; endemism; Espinhaço Range; orchid